IMF Research Bulletin, March 2009. (IMF Research Bulletin; IMF Research Bulletin ;, 2009)
IMF research summaries on measures of financial integration (by Martin Schindler) and on sovereign wealth funds and financial stability (by Tao Sun and Heiko Hesse); regional study on cross-border labor flows in new European Union member states (by Rudolfs Bems); listing of contents of Vol. 56 No. 1 of IMF Staff Papers, a special issue on frontiers of research on financial globalization; a listing of visiting scholars at the IMF during December 2008-March 2009; and a listing of recent IMF Working Papers.